2014
DOI: 10.1007/s00405-014-3444-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sublingual immunotherapy for house dust mite allergic rhinitis

Abstract: In the present study, we investigated the outcomes of sublingual immunotherapy (SLIT) in house dust mite-induced allergic rhinitis (HDM-AR) patients. In this prospective, multicentric study, 186 patients with AR who had positive skin prick test results for HDMs were included. The patients were administered SLIT using Staloral 300 for 1 year. Evaluation of the patients regarding symptom scores, clinical findings and Rhinitis Quality of Life Questionnaire (RQLQ) scores was performed at baseline, and then at 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…Traditionally, SCIT has been viewed as the golden standard for AIT, although SLIT has emerged as an effective and safe alternative 6. In recent years, there has been accumulating evidence for the efficacy and safety of AIT for AR, with several studies demonstrating both short-term efficacy8910 and long-term efficacy, using mainly SLIT 11121314. However, comparatively few studies have reported on the efficacy of AIT in Chinese AR patients, with the available data documenting the efficacy of SLIT in pediatric and adult AR patients 151617.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, SCIT has been viewed as the golden standard for AIT, although SLIT has emerged as an effective and safe alternative 6. In recent years, there has been accumulating evidence for the efficacy and safety of AIT for AR, with several studies demonstrating both short-term efficacy8910 and long-term efficacy, using mainly SLIT 11121314. However, comparatively few studies have reported on the efficacy of AIT in Chinese AR patients, with the available data documenting the efficacy of SLIT in pediatric and adult AR patients 151617.…”
Section: Introductionmentioning
confidence: 99%
“…SLIT has been reported to be well-tolerated and effective for the treatment of allergic rhinitis (AR) and asthma in children, adults, and elderly patients 1,2. Several systemic reviews indicate that the use of SLIT in patients with AR sensitive to house dust mites (HDMs) yielded significantly lower symptom scores and better clinical outcomes 3,4,5. Recent studies support the use of SLIT as the first-choice treatment for AR and asthma compared to medication and subcutaneous immunotherapy (SCIT) 6.…”
mentioning
confidence: 99%
“…O podobnych wynikach dokumentujących skuteczność Staloralu z alergenami roztoczy w astmie i/lub alergicznym nieżycie nosa donoszą autorzy innych badań [34,35].…”
Section: Alergia Na Roztocze Kurzu Domowegounclassified